2017
DOI: 10.1080/17429145.2017.1365179
|View full text |Cite
|
Sign up to set email alerts
|

Short-term UV-B radiation effects on morphology, physiological traits and accumulation of bioactive compounds in Prunella vulgaris L.

Abstract: Prunella vulgaris plants (full-bloom stage) were subjected to short-term (15 days) UV-B radiation in a growth chamber. UV-B radiation was effective at enhancing morphological and biomass characteristics and decreasing chlorophyll contents of P. vulgaris. Treatment of P. vulgaris with artificial UV-B radiation significantly increased peroxidase (POD), superoxide dismutase (SOD) and glutathione (GSH) activities compared to the control treatment. UV-B radiation significantly increased the levels of hydrogen perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…Agati et al [47] demonstrated that PAR favored the flavonoids accumulation especially the quercetin in the crop. UVA + UVB UV light increased phenolic and carotenoid contents in both varieties [25] Prunella vulgaris UV-B UV-B light increased total flavonoid, rosmarinic acid, caffeic acid content [69] In addition to UV light, visible light is another critical factor for vegetables and fruits growth. It is well known that blue light plays an important role in chloroplast development, chlorophyll formation and stomata opening, while red light is crucial to plant growth such as stem elongation, leaf expansion, and photosynthesis [48].…”
Section: Light Spectramentioning
confidence: 99%
“…Agati et al [47] demonstrated that PAR favored the flavonoids accumulation especially the quercetin in the crop. UVA + UVB UV light increased phenolic and carotenoid contents in both varieties [25] Prunella vulgaris UV-B UV-B light increased total flavonoid, rosmarinic acid, caffeic acid content [69] In addition to UV light, visible light is another critical factor for vegetables and fruits growth. It is well known that blue light plays an important role in chloroplast development, chlorophyll formation and stomata opening, while red light is crucial to plant growth such as stem elongation, leaf expansion, and photosynthesis [48].…”
Section: Light Spectramentioning
confidence: 99%
“…The depletion of the stratospheric ozone layer has become a serious global environmental problem that has led to an increase in the amount of ultraviolet-B radiation (UV-B, 280–320 nm) reaching the Earth’s surface, and the amount of UV-B radiation on the Earth’s surface will continue to increase in the coming decades [ 1 , 2 ]. In general, many studies have reported that UV-B radiation has harmful effects on the growth, physiology and productivity of plants [ 3 , 4 , 5 ]. However, in recent years, some studies have found that UV-B radiation can have beneficial effects on the secondary metabolism of medicinal plants [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds may play an important role as antioxidants by scavenging the free radicals produced under oxidative stress (Giorgi et al, 2009 andBernal et al, 2013). It is widely accepted that the metabolism of phenolic compounds is up-regulated by a wide range of environmental stresses, such as the UV-B radiation (Luis et al, 2007;Bernal et al, 2015;Shen et al, 2015;Zhang et al, 2017)…”
Section: Total Phenolic Compounds (Tpc)mentioning
confidence: 99%
“…UV-B radiation increased biomass in Ocimum basilicum L (Sakalauskaite et al, 2013),. Laurus nobilis L.(Bernal et al, 2015) and Prunella vulgaris L (Zhang et al, 2017). whereas, in Catharanthus roseus L (Guo et al, 2014),.…”
mentioning
confidence: 99%